2022-RA-1470-ESGO Is neoadjuvant chemotherapy effective as prehabilitation program in advanced epithelial ovarian cancer?. (20th October 2022) - Ghirardi, Valentina; Marchetti, Claudia; Ferrante, Maria Giulia; Faustini, Alice Zampolini; Scambia, Giovanni; Fagotti, Anna
Abstract : Introduction/Background: A consistent number of advanced ovarian cancer (AOC) patients present with poor performance status. We sought to determine whether neo-adjuvant chemotherapy(NACT) can modify pre-operative characteristics used to identify patients at high risk(HR) of peri-operative complications, as defined by the Mayo Clinic Algorithm Methodology: In this retrospective single center observational study, FIGO stage III-IV AOC patients undergoing NACT from 01/2016 to 12/2019 were collected and triaged as low risk(LR) and HR according to Mayo Clinic Algorithm. HR group included women with at least one of the following criteria:(i) Albumin <3.5 g/dL, (ii) age ≥80 years, (iii) age 75–79 with ECOG performance status >1, stage IV disease, or complex surgery required and (iv) ASA score ≥ 3. Pre-NACT and post-NACT characteristics were compared in the HR group. Results: 177 patients were included, 144(81%) and 33(19%) were classified as HR and LR respectively before NACT. A median number of 4 cycles (range 2–6) of carboplatinum-paclitaxel NACT was administered in HR patients, with bevacizumab addiction in 53% of cases. 115 out of 144 (80%) HR women showed a significant difference in pre-NACT ECOG (p=0.007), ASA score (p=0.001), albumin level(p=0.001) compared to post-NACT setting, taking on LR features. All patients underwent interval surgery and complete cytoreduction was achieved in 97 (84%) cases. Among 42 (35%) post-operative complications, 7(16%) were classified as G3-G4. Median progression free survival was 18 months (CI 95% 14 -21), median overall survival was 54 months (CI 95% 34–73) ( figure 1 ). Conclusion: NACT appeared to improve pre-treatment patient's characteristics that may account for an increase peri-operative morbidity. A comparison between the analyzed population and a statistically matched group of HR and LR patients undergoing primary debulking surgery is in due course.